Analytical and Experimental Determination of FML Stiffness and Strength Properties - Kamocka, Monika; Mania, Radosław J. (Wydawnictwo Politechniki Łódzkiej ; Katedra Dynamiki Maszyn - Wydział Mechaniczny Politechniki Łódzkiej, 2015)
The paper presents application of analytical methods of determining the mechanical properties of Fibre Metal Laminates. Chosen micromechanical methods were employed to predict elastic moduli and strength of FML panels. Prediction was conducted on two levels i.e. micromechanics where properties of a single composite lamina (prepreg) were analyzed, and macro-mechanics to determine properties of a full FML hybrid material. The properties of a single GFR lamina were predicted by Rule of Mixture Method (ROM), inverse Rule of Mixture Method with correction factor, Halpin Tsai Method, Tsai Method and Wilczynski Method application. Properties of full 3-2 FML lay-up were determined using the Rule of Mixtures. Analytical results were verified by experimental tests. Tensile and bending test were performed on rectangular standard coupons of 3-2 FMLs.
Keywords: FML; hybrid laminate; mechanical properties; mechanical testing; fibre metal laminates; laminat hybrydowy; właściwości mechaniczne; badania mechaniczne; laminaty z włókna metalowego